Adherence to Treatment in Psychotic Disorders - Development of user-centered mobile health intervention - Kauppi, Kaisa (Annales Universitatis Turkuensis D 1227, 2016)
The aim of this study was to explore adherence to treatment among people with psychotic disorders through the development of user-centered mobile technology (mHealth) intervention. More specifically, this study investigates treatment adherence as well as mHealth intervention and the factors related to its possible usability. The data were collected from 2010 to 2013. First, patients’ and professionals’ perceptions of adherence management and restrictive factors of adherence were described (n = 61). Second, objectives and methods of the intervention were defined based on focus group interviews and previously used methods. Third, views of patients and professionals about barriers and requirements of the intervention were described (n = 61). Fourth, mHealth intervention was evaluated based on a literature review (n = 2) and patients preferences regarding the intervention (n = 562). Adherence management required support in everyday activities, social networks and maintaining a positive outlook. The factors restricting adherence were related to illness, behavior and the environment. The objective of the intervention was to support the intention to follow the treatment guidelines and recommendations with mHealth technology. The barriers and requirements for the use of the mHealth were related to technology, organizational issues and the users themselves. During the course of the intervention, 33 (6%) out of 562 participants wanted to edit the content, timing or amount of the mHealth tool, and 23 (4%) quit the intervention or study before its conclusion. According to the review, mHealth interventions were ineffective in promoting adherence. Prior to the intervention, participants perceived that adherence could be supported, and the use of mHealth as a part of treatment was seen as an acceptable and efficient method for doing so. In conclusion, the use of mHealth may be feasible among people with psychotic disorders. However, clear evidence for its effectiveness in regards to adherence is still currently inconclusive.

Hoitoon sitoutuminen psykoottisissa häiriöissä - käyttäjälähtöisen mobiiliteknologisen intervention kehittäminen Tutkimuksen tavoitteena oli selvittää psykoottisia häiriötä sairastavien hoitoon sitoutumista, kehittämällä käyttäjälähtöinen mobiiliteknologinen interventio. Tutkimuksen kohteena olivat hoitoon sitoutuminen, mobiiliteknologinen interventio ja sen käytettävyyteen liittyvät tekijät. Aineisto kerättiin vuosina 2010–2013. Ensimmäisessä vaiheessa kuvattiin potilaiden ja hoitohenkilökunnan näkemyksiä hoitoon sitoutumisen hallinnasta ja sitä rajoittavista tekijöistä (n = 61). Toisessa vaiheessa määriteltiin intervention tavoite ja menetelmät ryhmähaastatteluiden sekä aiempien tutkimusten avulla. Kolmannessa vaiheessa kuvattiin potilaiden ja hoitohenkilökunnan näkemyksiä esteistä ja vaatimuksista intervention käytölle (n = 61). Neljännessä vaiheessa mobiiliteknologisia interventioita arvioitiin perustuen kirjallisuuskatsaukseen ja potilaiden (n = 562) mieltymyksiin. Hoitoon sitoutumisen hallinta edellytti arkielämän, sosiaalisten verkostojen ja positiivisen näkemyksen tukemista. Hoitoon sitoutumista puolestaan rajoitti sairauteen, käyttäytymiseen ja ympäristöön liittyvät tekijät. Intervention tavoitteeksi muodostui potilaan suunnitelmallisen pyrkimyksen tukeminen hoitosuositusten ja – ohjeiden noudattamiseksi, hyödyntäen mobiiliteknologiaa. Mobiiliteknologian käytön vaatimukset ja esteet liittyivät teknologiaan, organisaatioon ja käyttäjään. Kaikkiaan 562 tutkittavasta, 33 (6 %) halusi intervention aikana sisällöllisiä, ajallisia tai määrällisiä muutoksia valitsemiinsa viesteihin, ja 23 (4 %) keskeytti intervention tai tutkimuksen. Kirjallisuuskatsauksen mukaan mobiiliteknologiset interventiot eivät edistäneet hoitoon sitoutumista. Tutkittavat kuvasivat interventiota edeltävästi, että hoitoon sitoutumista on mahdollista tukea, ja mobiiliteknologia osana hoitoa koettiin hyväksyttäväksi ja tehokkaaksi menetelmäksi tähän. Arvioinnin perusteella mobiiliteknologia saattanee olla soveltuva osa psykoottista häiriöitä sairastavien hoitoon. Tieto mobiiliteknologian vaikuttavuudesta hoitoon sitoutumisen edistämiseksi on kuitenkin vielä tällä hetkellä puutteellinen.